SIMULASI SISTEM MANUFAKTUR Studi Kasus : Proses Produksi Brake Drum Coupling - Tritiya A.R. Arungpadang (Jurnal Tekno Mesin, 2015)
Now, manufacturing companies must develop their systems performance to the higher productivity level. There are many manufacturing system indicators, three of them are amount of output in a period of time, process lead time, and work in process. Those indicators will be viewed as a result of production machine resources allocation in each work station. The discrete system simulation was used to represent the real system. Using Arena software, we will get details information about the characteristic of each system variables that can used to improve the system performances without interrupt the real system itself. This paper explained briefly manufacturing systems simulation and its result for some operational strategies of production machine allocation.*corresponding author, e-mail address: tritiya_arungpadang@unsrat.ac.id